Advanced electromagnetic analysis of passive and active planar structures - Rozzi, T. (Tullio); Farina, Marco Ph.D. (London, United Kingdom Institution of Electrical Engineers, 1999)
The book has 6 chapters. Appendices are given at the end of the book. The following topics are discussed: fundamentals of electromagnetics; propagation in closed waveguides; ideal planar waveguides on multilayered substrate: 2D analysis; passive and active planar waveguides on multilayered substrate: 2D analysis; and passive and active planar waveguides on multilayered substrate: 3D analysis.
Electronic reproduction.
Keywords: Microwave integrated circuits -- Mathematical models; Electric filters, Passive -- Mathematical models; Electric filters, Active -- Mathematical models; Electronic books